The effect of intraventricular injections of noradrenaline, 5-hydroxytryptamine, acetylcholine and tranylcypromine on the ox (Bos taurus) at different environmental temperatures - Findlay, J. D. (1968)
1. Noradrenaline, 5-hydroxytryptamine (5-HT), acetylcholine and tranylcypromine were injected or infused into the lateral ventricle of the ox. The effects of these drugs on heart and respiration rates, heat production, rectal, skin and hypothalamic temperatures and skin evaporative loss were measured when the animal was exposed to environmental temperatures ranging from -1° C to +30° C. 2. Acetylcholine (0·001-2 mg) had no detectable effect on temperature regulation at 20° C. 3. In small doses (0·005-0·05 mg) 5-HT had no detectable effect. Larger doses (2-5 mg) given in a cold environment (-1° C) also had no effect but the same doses given in warm environments (15-30° C) caused increases in skin temperatures, skin evaporative loss and respiratory rate, and decreases in rectal and hypothalamic temperatures. 4. Infusion of tranylcypromine (0·107 ml./min of a 1 in 50 solution) in a warm environment (20° C) also caused a decrease in rectal temperature after a delay of 1-1½ hr during which no effects were apparent. 5. Noradrenaline (2 mg) had no effect on temperature regulation when injected into animals in a warm environment (30° C). When injected (1 mg) into animals in a cold environment (-1° C) shivering stopped and heat production and rectal and hypothalamic temperatures were decreased. 6. It is concluded that intraventricular 5-HT and noradrenaline both cause a decrease in body temperature, and it is unlikely that central temperature regulation in the ox is mediated only by these two substances.